Telling tales: sharing humorous education stories to enhance teacher wellbeing and learning. Issue 2 (4th March 2023) - Mead, Nadia
ABSTRACT: Sharing personal teaching stories provides opportunities for enhanced wellbeing and learning for both experienced and pre-service teachers. This paper shares the results of a qualitative pilot study that used narrative inquiry to collect and share teacher stories. The research was conducted in two phases. The first phase collected humorous stories from experienced teachers recalled from the first years of their teaching career. Thematic data analysis investigated the wellbeing and learning impact on those teachers when sharing their stories. The second phase invited pre-service teachers to read and evaluate the impact of humorous stories when preparing for their first school placements. Thematic data analysis investigated the wellbeing and learning impact on pre-service teachers reading these stories. The analysis from both phases demonstrated recurring themes regarding the importance of teacher-student relationships for teacher wellbeing. The results also showed that the sharing and reading of stories had beneficial outcomes such as enhanced wellbeing and enhanced learning for both the teacher storytellers and the pre-service teacher readers. This study provides evidence that the inclusion of real-life stories offers a valuable addition to Initial Teacher Education programs as a way of developing professional and reflective practice.